Zeolite and its effect on nitrogen efficiency in rice and corn - Soca, Miguel; Daza T., Martha Constanza (Revista de Ciencias Agrícolas, 2015)
This study evaluated the effect of zeolites on ammonia volatilization reductions (AVR) and leaching volume (LV), as well as on rice Oryza sativa L. and maize Zea mays L. yields. The first experiment was conducted in a completely random design (CRD) and evaluated the influence of zeolite particle size (<1 mm, 1 - 2 mm, 2 - 3 mm, and 3-5 mm) on AVR. The second experiment evaluated VL in the application of four treatments: control (T), zeolite (Z), urea (U), and urea + zeolite (UZ). The third experiment was conducted in rice and evaluated the effect of two application methods (random spread and transplantation) and four treatments (T, U, UZ 10% and UZ 15%) on crop yield. The fourth experiment was conducted in a corn crop using two treatments (U and UZ15%), there crop yield in two soils (alluvial and skeletal) was evaluated. Particle sizes between 3 and 5 mm showed an AVRof 50% and LV of 48%. Zeolites application in rices howed an AVR of 60% and increased yields with out differences between application methods. Its application also improved grain weight. Zeolites improved the efficiency of nitrogen fertilization.